Pembinaan dan Pendampingan e-Marketing Pada Pengembangan Wisata Goa Pertapan di Desa Sedayu Gunung Kecamatan Besuki Kabupaten Tulungagung - Edi Murdiyanto; Diana Ambarwati (ABDI SABHA (Jurnal Pengabdian kepada Masyarakat), 2021)
This community service activity is carried out in Sedayu Gunung Village, Besuki District, Tulungagung Regency. This community service activity involved 17 people. The tourism potential that is the mainstay of the community in the area is a cave which is commonly called Goa Pertapan. There are several things that need to be considered, including locations that are not widely known by tourists, there is no installation of road signs, there are no directions either in google maps or manual directions and road access is still not good and there are many potholes. In addition, from a physical point of view, the room arrangement is not well ordered, electricity is not ready, so there is still no lighting and general access is not yet open for visitors. The goal is to provide assistance, create marketing concepts, publication and online marketing. This activity was carried out from May to November 2019, by contributing coaching and mentoring in the form of Internet Marketing training for partners in their development on social media that will be developed. In the future, the managers should improve management and separate between tourism management and village administration. In the development of Goa Pertapan tourist destinations, the main concept carried is the concept of historical tourism, this historical tourism concept describes the history of Goa Pertapan and the legends that exist and develop in the community combined with tours with the concept of outbound packages and local culinary potential. This concept is marketed online or offline media.